Percutaneous biliary approach as a successful rescue procedure after failed endoscopic therapy for drainage in advanced hilar tumors. Issue 4 (April 2017) - Jang, Sung Ill; Hwang, Jin‐Hyeok; Lee, Kwang‐Hun; Yu, Jeong‐Sik; Kim, Hee Wook; Yoon, Chang Jin; Lee, Yoon Suk; Paik, Kyu Hyun; Lee, Sang Hyub; Lee, Dong Ki
Abstract: Background and Aim: Palliative endoscopic or percutaneous biliary drainage is used for unresectable advanced hilar cancer (HC). The best option for drainage in Bismuth type III or IV HC has not been established. The aims of this study are to identify factors predictive of endoscopic stenting failure and evaluate the effectiveness of rescue percutaneous stenting in patients with advanced HC. Methods: Data from 110 patients with inoperable advanced HC were retrospectively reviewed. All received bilateral self‐expandable metallic stents. Patients were divided into three groups: I, successful initial endoscopic stenting; II, unsuccessful initial endoscopic stenting, followed by percutaneous stenting; and III, initial percutaneous stenting. We analyzed clinical results and radiologic tumor characteristics. Results: Baseline characteristics and clinical outcomes of all groups were similar, except the hospital stay was longer in group III than group I. Technical success rate was higher in groups II and III (100%) than in group I (72.4%). The functional success rate, stent patency time, patient survival time, and complication rate were similar between groups. Endoscopic stenting failed because of guide‐wire passage failure ( n = 12) or stent passage failure ( n = 7). The only factor significantly associated with endoscopic failure was a smaller left intrahepatic duct–common bile duct angle. Conclusions: As clinical outcomes were generally similar between approaches, percutaneous stenting is recommended for patients with Bismuth type III or IV advanced HC. Acute left intrahepatic duct–common bile duct angulation predicts endoscopic stenting failure. If endoscopic stenting fails, immediate conversion to the percutaneous approach is a necessary and effective rescue method.